Quantification of spinning® bike performance during a standard 50-minute class - Caria, M. A.; Tangianu, F.; Concu, A.; Crisafulli, A.; Mameli, O. (Journal of Sports Sciences, 2007)
Spinning is a type of indoor fitness activity performed on stationary bikes by participants who pedal together to the rhythm of music and the motivating words of an instructor. Despite worldwide popularity of this type of recreational activity, to date there have been few, mainly non-scientific, studies of the impact of spinning on metabolic, respiratory, and cardiovascular functions. The main aim of this study was to evaluate a number of metabolic and cardiovascular variables during a standard 50-min class performed by Spinning® instructors of both sexes: six males (age 30 ± 4.8 years, body mass index 24 ± 2.5 kg · m-2; mean ± s) and six females (age 34 ± 6.3 years, body mass index 21 ± 1.9 kg · m-2). The mean power output, heart rate, and oxygen uptake during the performance were 120 ± 4 W, 136 ± 13 beats · min-1, and 32.8 ± 5.4 ml · kg-1 · min-1 respectively for males, and 73 ± 43 W, 143 ± 25 beats · min-1, and 30 ± 9.9 ml · kg-1 · min-1 respectively for females. Analysis of individual performances showed that they were compatible with physical exercise that ranged from moderate-to-heavy to very heavy, the latter conditions prevailing. The results show that this type of fitness activity has a high impact on cardiovascular function and suggest that it is not suitable for unfit or sedentary individuals, especially the middle aged or elderly, who are willing to begin a recreational physical activity programme.